Development and implementation of a surgery management system aimed at a university hospital - Silva, Romero de Melo (2023)
Objectives: To develop and implement the surgical management system containing the Surgical List and Surgical Map. Method: This study is of exploratory and descriptive nature of the applied methodological research type. The methodology used is based on the software development process based on the Pressman system development life cycle model. Results: The system was developed and made available on all hospital computers on its internal network. Implemented in all surgical areas and Surgical Center. Conclusion: The surgical management system provides real-time information on surgical patient information to all departments involved with surgical patients.